The Critical Analysis of the Discursive Practices of a Discourse “Case Study: President Barak Obama’s Final Speech” - BESSAOUDI ,Boualem; TOUHAMI ,A. Ibtissem (Faculty of Letters and Foreign Languages Department of English, 2017)
This study deals with investigating language in use, by decoding the hidden meanings of the president Obama’s final speech in the White House Correspondents Dinner 2016. The analysis is built upon two approaches to discourse analysis, first the critical discourse of Fairclough framework on the speech that examines a variety of concepts that flow and came across three dimensional model. The second approach explore pragmatically the president intention’s hidden meanings through Brown and Yule (1983) pragmatic tools such as presupposition, inference, implicature, and schematic knowledge. The study draws attention to those specific approaches to project the framework on the discourse and to describe how this speech is important an American social practice in politics, and to defend ideologies, which contains exchange of knowledge, social identities, and social practices within culture. A set of quotations has been selected from the speech for analysis by both critical discourse and pragmatic approaches